2020
DOI: 10.1038/s41467-020-19330-7
|View full text |Cite
|
Sign up to set email alerts
|

Conformational disorder of organic cations tunes the charge carrier mobility in two-dimensional organic-inorganic perovskites

Abstract: The chemical nature of the organic cations governs the optoelectronic properties of two-dimensional organic-inorganic perovskites. But its mechanism is not fully understood. Here, we apply femtosecond broadband sum frequency generation vibrational spectroscopy to investigate the molecular conformation of spacer organic cations in two-dimensional organic-inorganic perovskite films and establish a correlation among the conformation of the organic cations, the charge carrier mobility, and broadband emission. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 71 publications
(95 reference statements)
2
86
0
Order By: Relevance
“…Advanced Energy Materials published by Wiley-VCH GmbH being reported. Interestingly, the hole mobility of about 2 × 10 -4 cm 2 V −1 s −1 obtained for the shortest barrier length of 1.4 nm is quite similar to the above discussed study by Li et al, [18] whilst the electron mobility is consistently one order of magnitude lower.…”
Section: (18 Of 26)supporting
confidence: 88%
See 3 more Smart Citations
“…Advanced Energy Materials published by Wiley-VCH GmbH being reported. Interestingly, the hole mobility of about 2 × 10 -4 cm 2 V −1 s −1 obtained for the shortest barrier length of 1.4 nm is quite similar to the above discussed study by Li et al, [18] whilst the electron mobility is consistently one order of magnitude lower.…”
Section: (18 Of 26)supporting
confidence: 88%
“…[244] This is indeed the case for linear aliphatic spacers with varied length, as shown by Li et al Here, both in-plane and out-of-plane charge carrier mobility clearly increases with the reduction of interlayer distance, with the exception of BA 2 PbI 4 . [18] From the series of n-alkyl cations, Li et al found hexylammonium HA to show the highest in-plane (1.5 cm 2 V −1 s −1 ) and out-of-plane mobility (3 × 10 -4 cm 2 V −1 s −1 ) due to the combination of low interlayer distance and non-distorted carbon chain, as further discussed in below. [18] For LPKs based on aromatic spacers SCLC measurements also show a trend of increase in both hole and electron mobilities with the reduction in d-spacing.…”
Section: Barrier Widthmentioning
confidence: 91%
See 2 more Smart Citations
“…The merit suggests the 2D perovskites are particularly suitable for application of light-emitting diodes (LEDs). In 2D perovskites, a broadband emission with large stokes shift is also observed, which is proposed for the potential applications of white light display and lightening (Dohner et al, 2014a,b;Smith et al, 2017;Smith and Karunadasa, 2018;Li C. et al, 2020). In addition to efficient light emission, the transport of charge carriers is also pivotal for the performance of an optoelectronic device which, however, is limited in 2D perovskites.…”
Section: Introductionmentioning
confidence: 99%